Principals’ instructional time management and students’ academic performance in secondary schools in Ondo North senatorial district of Ondo State, Nigeria - Adeolu Joshua Ayeni (Journal of Education and Learning (EduLearn), 2020)
The persistent concern of stakeholders in the education sector over the dwindling academic performance of students in Nigerian secondary schools could be attributed to the perceived inadequacies in instructional time management. This study therefore investigated principals’ instructional time management strategies, teachers’ effectiveness in instructional tasks, and students’ academic performance in secondary schools in Ondo North Senatorial District of Ondo State, Nigeria. Descriptive design of the survey type was adopted. Multi-stage sampling technique was used to select 30 public secondary schools from three (3) Local Government Areas in the Northern Senatorial Districts of Ondo State. The sample comprised 600 teachers and 30 principals randomly selected for the study. Three (3) research questions were answered using frequency counts and percentage, while three (3) hypotheses were tested using Pearson Product Moment Correlation (PPMC) at 0.05 level of significance. Findings indicated a significant relationship between principals’ time management strategies and teachers’ instructional tasks performance (r-cal=0.622, p less than 0.05), there was significant relationship between principals’ time management strategies and students’ academic performance (r-cal=0.702, p less than 0.05), and significant relationship between teachers’ instructional tasks performance and students’ academic performance (r-cal=0.587, p less than 0.05). The major constraints to instructional time were pressure of administrative duties and excess workload. Based on the findings, it was recommended that principals should step-up efforts at prioritizing administrative tasks, encouraging teamwork in instructional activities and delegating duties to the experienced teachers in the management cadre to reduce excess workload, and improve monitoring and evaluation of teachers’ instructional tasks performance for better academic performance of students in secondary schools.